Rancang Bangun Aplikasi E-Commerce untuk UMKM Konveksi - Ahmad Satriadi; Supriyatna Supriyatna (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research presents the development of an e-commerce application aimed at enhancing the operational efficiency of Khadijah Konveksi, a small and medium-sized enterprise (SME) in the garment industry. The application, developed using Android, Java, and Kotlin, provides features for order management, real-time tracking, and online payment, significantly improving customer experience and operational workflow. Initial feedback indicates a high level of customer satisfaction and a notable increase in operational efficiency. The project also highlights the collaborative efforts between students, faculty, and industry professionals, demonstrating the impact of academic-industry partnerships in driving technological advancements for SMEs